149k views
0 votes
Multiply (x+1)^2

a. x^2+1
b. x^2+2x+2
c. x^2+x+1
d. x^2+2x+1
PLEASE HELP

2 Answers

3 votes

Answer:

d. x^2 + 2x + 1

Explanation:

(x+1)(x+1)

use the FOIL method:

x^2 +1x +1x +2

combine like terms 1x and 1x

x^2 +2x +1

User Pavlo Datsiuk
by
4.3k points
2 votes

Answer:

D

Explanation:

We have:


(x+1)^2

Expand:


=(x+1)(x+1)

Distribute Property:


=(x+1)x+(x+1)(1)

Distribute:


=x^2+x+x+1

Add:


=x^2+2x+1

Hence, our answer is D.

User Febi M Felix
by
4.8k points